2020
DOI: 10.1039/d0cp05016d
|View full text |Cite
|
Sign up to set email alerts
|

Orientation and dynamics of Cu2+based DNA labels from force field parameterized MD elucidates the relationship between EPR distance constraints and DNA backbone distances

Abstract: Pulsed electron paramagnetic resonance (EPR) based distance measurements using the recently developed Cu(II)-DPA label present a promising strategy for measuring DNA backbone distance constraints. Herein we develop force field parameters...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 96 publications
0
13
0
Order By: Relevance
“…11 The labeling of DNA with Cu(II) is described in ESI. † 11,14 Electrophoretic mobility shi assays (EMSA) show that CueR binds to the DPA-DNA duplex (Fig. S1 †).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 The labeling of DNA with Cu(II) is described in ESI. † 11,14 Electrophoretic mobility shi assays (EMSA) show that CueR binds to the DPA-DNA duplex (Fig. S1 †).…”
Section: Resultsmentioning
confidence: 99%
“…Prior work has shown that the Cu(II)-Cu(II) distance in DNA can be directly related to the backbone C 0 -C 0 distance. 14 A more careful model analysis that accounts for the positioning of the Cu(II) atoms with respect to the DNA backbone, yields a 5 0 endcenter -3 0 end angle of 55 for the duplex with a 3.6 nm Cu(II)-Cu(II) distance (Fig. S8 †).…”
Section: Resultsmentioning
confidence: 99%
“…The experimental most probable distance is consistent with the prediction of C′–C′ and Cu 2+ –Cu 2+ distances from a 2.0 μs Molecular Dynamics (MD) simulation. Note that previous work has shown that a MD trajectory of such a length is sufficient to reasonably estimate the most probable distance but may not be sufficient to capture the full distribution width due to slow mobility of the DPA side chains …”
mentioning
confidence: 99%
“…Note that previous work has shown that a MD trajectory of such a length is sufficient to reasonably estimate the most probable distance but may not be sufficient to capture the full distribution width due to slow mobility of the DPA side chains. 43 In summary, we present a systematic examination of factors that enhance the phase memory times for Cu 2+ labels. In particular, we show that deuteration of the solvent and cryoprotectant can provide improvements that allow for the rapid measurement of distances up to 6.7 nm.…”
mentioning
confidence: 99%
“…1,76 This concept was further developed and validated through EPR experimentation combined with MD simulations enabled by force field parametrization of the Cu 2+ −DPA motif. 80 These MD simulations revealed that the DPA residue resides within the helix of a DNA, at an angle roughly perpendicular to the DNA backbone. This orientation, shown in Figure 7A, is comparable to natural DNA bases.…”
Section: For Cu 2+ Labeling Of Dnamentioning
confidence: 99%